11% efficiency solid-state dye-sensitized solar cells with copper(II/I) hole transport materials - Yiming Cao (Nature Portfolio, 2017)
Inadequate pore infiltration and low conductivity of hole transporter materials limit the performance of solid-state dye-sensitized solar cells. Using fast charge-exchange Cu(II/I) complexes as part of the hole transporting material, Caoet al. overcome these issues to achieve a record photoconversion efficiency of 11%.